Ascorbic Acid Encapsulation in Hydrophobic Silica Xerogel - Revuelta, Mariana Valeria (2011)
Self-assembled hybrid organo-silica sol-gel materials are rapidly expanding for new and novel applications. The microporous solid silica matrix was used as carrier for the controlled release of Ascorbic Acid (AA), selected as molecule cargo model. One-step synthesis procedure was optimised for preparation of silica–molecule composites by using tetraethoxysilane and methyltrimethoxysilane as precursors. The hydrophobic silica xerogel matrices were characterized by Fourier transformed infrared spectroscopy (FTIR) and X-ray diffraction. Specific surface area and porosity parameters were determinated by Brunauer-Emmet-Teller (BET) technique and the matrix surface morphology by Scanning Electron Microscopy (SEM). The observed release pattern could be interesting for the development of AA-fortified food and to be used in food packaging.